THE SCHOOL AS A PLACE FOR BEGINNING TEACHERS' TRAINING - Miriane Zanetti Giordan; Marcia de Souza Hobold (Editora da Universidade de Santa Cruz do Sul, 2016)
This article discusses the formation in school environment and the aims to discuss the training in service of beginning teachers. Interviews were conducted with 22 beginning teachers of Elementary School's final years and the qualitative approach guided the investigation process. Theoretically support this research the following authors: Demailly-Chantraine (1992), Nóvoa (1997, 2009) and Canário (1998) among others. The results revealed that beginning teachers were well received in schools and that they are accompanied in their work, mainly by the school supervisor, which facilitates greatly the training in service of these teachers. What else contributes to the formation of the beginning teachers is the sharing and the exchange of ideas and experiences with the workmates. These features allow us to consider the school as a formation space for being constitutor of knowledge and practices teachers.